Pengaruh Konsentrasi Kalium Permanganat Terhadap Karakteristik Pisang Ambon (Musa paradisiaca var. sapientum (L.) Kunt.) Selama Penyimpanan - Ningrumsari, Ida; Putranto, Kelik; Anggraeni, Tharisa (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Bananas are the fruit with the highest production in Indonesia, but quality disintegration often occurs during the distribution process. Therefore, it is necessary to maintain the quality and shelf life of bananas during the distribution process by using potassium permanganate as a ripening inhibitor. The purpose of this research was to study the effect of potassium permanganate concentration on the characteristics of ambon banana during storage. This research was conducted at the Chemistry Laboratory of the Faculty of Agriculture, Ma'soem University from January to March 2023 The method used in this study used a Randomized Block Design (RAK) with various concentrations of potassium permanganate 0% as control, 2%, 4%, 6%, 8% and 10%. The parameters observed during storage were physico-chemical parameters consisting of peel color scale index, weight loss, moisture content, total acid, vitamin c, and total soluble solids, and sensory parameters, namely the level of liking for aroma, taste, and texture of ambon bananas. The results showed that different concentrations of potassium permanganate significantly affected the characteristics of ambon bananas during 7 days storage. The use of 6% potassium permanganate concentration was the most effective and economical in maintaining the characteristics and shelf life of ambon banana 4 days longer than the control.